Avaliação do fenótipo de persistência em isolados nasocomiais de Acinetobacter calcoaceticus-baumannii - Gallo, Stephanie Wagner (2017)
Acinetobacter calcoaceticus-baumannii (ACB) complex comprises opportunistic and emerging pathogens that are responsible for several diseases, mainly affecting immunocompromised patients and those hospitalized in intensive care units. Therapeutic options for ACB infections are restricted, since these microorganisms are often resistant to most antimicrobials. In addition, these bacteria may also form persister cells, which constitute a small population of susceptible cells able to survive lethal concentrations of bactericidal antimicrobials and other stressors. This phenotype is associated with failure in antimicrobial therapy, especially in chronic and recurrent infections. Therefore, the aim of this study was to evaluate the presence of persister cells from ACB complex isolates exposed to meropenem and/or polymyxin B, in biofilm and planktonic cells, as well as to analyze these cells regarding their morphology and identify expression patterns of proteins possibly involved in the formation and maintenance of persistence. For this, 20 clinical isolates were characterized for the ability to form biofilm on polystyrene surface, and for meropenem and polymyxin B susceptibility, by the assessment of Minimum Inhibitory Concentration (MIC). All isolates were exposed to meropenem at different concentrations above the MIC, while five isolates were exposed to polymyxin B for the assessment of the persisters presence. For all experiments, in order to estimate the fraction of remaining cells, aliquots were removed at determined time points, followed by serial decimal dilutions and drop plating technique on nutrient agar. All isolates presented persisters at different proportions, in both culture conditions when exposed to meropenem or polymyxin B after 48 h. The higher fractions were verified in biofilm for both antimicrobials in comparison with planktonic cultures. Meropenem concentrations did not influence persisters levels. However, after polymyxin B exposure, persister cells fractions were dependent on the concentration employed. After 24 h polymyxin B exposure, a growth resumption of surviving cells was observed. These cells were again evaluated for susceptibility to this antimicrobial, remaining susceptible with MIC of 1 μg/ mL. Moreover, integrity of polymyxin B in the supernatant of the cultures was verified by chromatographic assay, demonstrating that polymyxin B is not significantly degraded after 48 h exposure. On the other hand, when meropenem and polymyxin B were associated at different concentrations, no resumption of cell growth was observed, as well as this combination was able to eradicate persister cells from A. baumannii (Acb-1) cultured in late exponential phase. Furthermore, Nano-Liquid Chromatography Coupled to Tandem Mass Spectrometry was employed for the identification and relative quantification of proteins possibly associated with persistence in A. baumannii, after exposure to meropenem. Different patterns of expression were identified between persister cells present in planktonic and biofilm cultures, suggesting that persistence may be regulated by different mechanisms. Proteins involved in the cell division and DNA replication were overexpressed in planktonic persisters, in agreement with the electron scanning microscopy images that presented dividing cells in this culture condition. Overexpression of glucose dehydrogenase (GDH), NADH dehydrogenase 1 (NDH-1), succinate dehydrogenase and ATP synthase indicates the electron transfer from the GDH-catalyzed reaction to the electron transport chain as a possible energy source for persisters, supporting the presence of cell division observed in planktonic culture. Conversely, proteins involved in amino acid metabolism, as well as major elongation factors were underexpressed in Acb-1 persister cells, suggesting that protein synthesis is reduced, even though many proteins were overproduced. Increased expression of several membrane-related proteins has also been observed, indicating possible changes in its composition and function, although proteins related to lipid metabolism were underexpressed. Overall, proteomic analysis of the persister cells showed that these cells could be physiologically distinct when cultured under different conditions, as well as overtime in the same condition. Therefore, considering the different behaviors of Acb-1 when exposed alone to meropenem or polymyxin B, as well as when exposed to these drugs in combination, it was concluded that each antimicrobial might act as a different stressor, possibly leading and/or selecting distinct tolerance mechanisms among persisters, which enabled their eradication when the drugs were combined.